Remote Sensing in Agriculture: State-of-the-Art - Borgogno-Mondino, Enrico; Tarantino, Eufemia; Capolupo, Alessandra (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Special Issue on "Remote Sensing in Agriculture: State-of-the-Art" gives an exhaustive overview of the ongoing remote sensing technology transfer into the agricultural sector. It consists of 10 high-quality papers focusing on a wide range of remote sensing models and techniques to forecast crop production and yield, to map agricultural landscape and to evaluate plant and soil biophysical features. Satellite, RPAS, and SAR data were involved. This preface describes shortly each contribution published in such Special Issue.